Efeitos musculares promovidos pelo treinamento resistido em ratas ovariectomizadas - Canevazzi, Gustavo Henrique Rigo (2014)
Menopause is highly associated with the increase of several metabolic disorders. In addition menopause promotes accelerated loss of muscle strength and mass, process known as sarcopenia, generating a deleterious role in the performance of physical functions. In this sense, resistance training has been recommended for the treatment of numerous diseases associated with menopause, as well as sarcopenia, as a nonpharmacological intervention. The aim of this study was to investigate the effects of the resistance training using the vertical ladder as a model on the muscle cross-sectional area and the percentage of muscle fiber types in the plantaris muscle of intact or ovariectomized rats and/or under hormone reposition therapy. Holztman adult female rats were distributed in 7 groups: Sham operated sedentary (Sham-Sed), Sham operated resistance trained (Sham-Tr), Ovariectomized sedentary (Ovx-Sed), Ovariectomized resistance trained and hormone reposition (Ovx-Tr-TRH), Ovariectomized sedentary and hormone reposition (Ovx-TRH), Ovariectomized resistance trained (Ovx-Tr), Ovariectomized and placebo reposition (Ovx-TRH-Pl). During a 12-week resistance training the animals climbed the vertical ladder of 1.1m with weights attached to their tails. Each session was carried out every 72 hours with 4-9 climbs. The ovariectomy promoted a reduction in cross-sectional area of the type I and II fiber when compared to Sham-Sed group, whereas the resistance training in the ovariectomy (Ovx-Tr group) was able to increase the cross-sectional area of the two fiber types (p<0.05). Moreover, TRH did not prevent the reduction of cross-sectional area of the type II fiber however it attenuated the reduction in cross-sectional area of type I fiber. The ovariectomy, hormone reposition and resistance training had no effect into promote alterations in the absolute number of muscle fiber types of the plantaris muscle and there was no correlation in the percentage of fiber muscle types. Our results indicate that resistance training can be a useful tool to prevent skeletal muscle mass reduction induced by ovariectomy.